Constructing Customary Citizenship: Ritual, Sanctions, and Recognition in an Old Balinese Village - I Wayan Sukabawa; Pande Putu Toya Wisuda; I Made Wirajana; Ni Ketut Sri Rahayuni (Universitas Udayana, 2026)
Debates on community governance increasingly examine micro-practices that generate compliance without coercion. This study analyzes the marebu agung marriage completion ritual in an Old Balinese (Bali Aga) village, Desa Adat Binyan (Binyan Customary Village), Kintamani District, as a disciplinary mechanism that structures differentiated forms of customary citizenship. Based on a twelve-month ethnographic case study using observation, interviews, and analysis of awig-awig (customary regulations), the research shows that ritual choreography shapes subjects through regulated bodily action. Temporal deadlines and escalating material sanctions sustain compliance, while horizontal social visibility encourages mutual monitoring. The tripartite krama (customary membership categories) system withholds full recognition until ritual completion, linking marital legitimacy to community membership. Using Foucauldian analytics, the study demonstrates how sacred ritual operates as a technology of power within customary governance, contributing to global discussions on ritualized citizenship and non-state disciplinary systems.